The Word Formation of Blending in Humor Language: A Study of a Twitter Account “9GAG” - Sylvia, Rizka; Fitrisia, Dohra (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
The purposes of this study were to analyze the blended words found in 9GAG posts on Twitter in conveying humor and discover their meanings. This study applied a qualitative descriptive approach. The data were collected from 9GAG posts containing blended words in conveying humor through observation and documentation analysis. The study's findings indicated that there were 15 blended words found in 9GAG posts in conveying humor. Furthermore, the meanings obtained by the researchers differ as well. Many words were semantically similar to those listed in dictionaries, while others had an unconventional meaning, which can be used and interpreted only in certain contexts. Additionally, these findings were useful as language updates by listing new words discovered in the dictionary. It can rapidly enhance people’s linguistic understanding, especially EFL teachers and students who teach and learn English using this account. So, the misinterpretations and ambiguities that occurred this time could be minimized.